Speaking Extra. A resource book of multi-level skills activities + CD audio - Gammidge, Mick (Cambridge Cambridge University press, 2008)
Speaking Extra ia a lively collection of photocopiable speaking activities designed for use with young adults and adults.
Contents.
Keywords: Language; Learning; vocabulary; Activities; English - foreign language